First Principle Design Load Estimation for LH2 Fuel Tanks by Means of 0D Approach - Lampe, Tobias; Okpeke, Bright E.; Roß, Lukas; Ehlers, Sören (Volume 5: Ocean Engineering, 2023)
Within the framework of the Sustainable Development Goals, the United Nations (UN) General Assembly has declared its firm intention to combat climate change and the associated changes in the environment. Shipping is an important factor since its exhaust gases account for just over two percent of global green-house gas (GHG) emissions. This is reflected in the GHG Strategy of the International Maritime Organization (IMO), which forces the maritime industry to move away from fossil fuels towards zero-carbon alternatives. Liquid hydrogen is a promising candidate to enable this transition. As of now, class approval for the required technology is based on an alternative design approach which entails operational scenario development. In this work, a simulation-based approach for the estimation of design loads with respect to liquid hydrogen fuel tanks is presented. The MATLAB software is employed to implement a 0-dimensional approach for the calculation of the bulk thermodynamic behavior. Necessary thermodynamic quantities are obtained via internal energy by means of the CoolProp package. Vapor and liquid phases are treated separately under the assumption of a satu- rated liquid state while the vapor is allowed to superheat. There is good correlation between validation data and simulation. In order to provide a realistic load assessment during a ship voy- age, an exemplary cruise ship and corresponding power-demand profiles are utilized. The results are then analyzed with regard to occurring loads and operational efficiency